Design and development of 3D visual mapping system for elevator shaft inspection - Ong, Eng Hui (2019)
Elevator is an important vertical transportation system in Singapore as a highly urbanized country with limited geographical land. There are about 79.9% of the residents are staying in high-rise building. With population gradually increasing each year, due to limited land, more and more high-rise building is being built to accommodate the increased in population. Thus, elevator services becoming more and more important. However, more and more elevator in residential building has been plaguing with malfunctioning and erratic behavior which causes injuries or even death. This has led to tightening of elevator inspection and maintenance for public safety. The current inspection method involves labor intensive manual inspection, which compromises the safety of the inspector and causes delay in down time. In this thesis, the design and development of an 3D visual elevator shaft inspection system concept is proposed, which has potential to improve the yield and speeds up the elevator shaft inspection process. The proposed system is a scanning system that can be hoisted down the elevator shaft via pully system to capture the 3D and 2D information of the elevator shaft, which eventually be used for offsite inspection. A prototype is built, and it is tested in a hallway simulated as a vertical elevator shaft. It is found out that the proposed concept method is technically feasible for elevator shaft inspection with added benefits, however there are some improvement that can be made before full deployment for real operation.